The Egyptian box - Curry, Jane Louise (New York : Margaret K. McElderry Books, 2002)
Tee is happy to find that the ancient Egyptian box she inherits holds a spirit who will serve her, until she notices changes in her servant's appearance and behavior.
4.4
3-6
Keywords: Supernatural -- Fiction; Magic -- Fiction; Egypt -- Antiquities -- Fiction; Southwest, New -- Fiction; Supernatural -- Fiction; Magic -- Fiction; Egypt -- Antiquities -- Fiction; Southwestern States -- Fiction